EXPLORING PRE-SERVICE TEACHERS’ PERCEPTION TOWARDS TEACHER PROFESSIONAL DEVELOPMENT - Raisa Fadilla (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2020)
Considering the role of teachers which is uneasy, it is necessary to develop an effective means of supporting and retaining teachers to provide good quality learning environment for students and a supportive work environment for teachers. Based on the urgency of professional development for teachers, pre-service teachers’ perception towards teacher professional development (TPD) becomes prominent to explore. The survey reflects the pre-service teachers’ perception with regard to professional development.  The perception covers the most needed topics in TPD and the most needed learning activities which may give high impacts to their knowledge for teaching. This study involves pre-service teachers from English Department Batch 2016 who were taking internship program as English teachers in public or private schools in Banjarmasin.Regarding the pre-service teachers’ perception related to the needed topics, classroom management and knowledge of instructional practices in their subject field are the greatest area of development need followed by knowledge of their main subject and also ICT skills. On the concern of pre-service teachers’ perception related to most needed learning activities of TPD, courses or workshops is recognized as the most beneficial learning activities to improve teachers’ competences.The results of this study are expected to provide the basic thought for the implication for teacher preparation program in the future. Furthermore, the targeted implementation of the findings will give insights on the most needed professional development topics and most preferred learning activities which can be considered by the related institution when conducting teacher preparation program.